DRYING OF OKRA BY INFRARED RADIATION - Tanta, Seda; Doymaz, Ibrahim (YILDIZ TECHNICAL UNIV, 2019)
In this study, we tried to evaluate mass transfer during an infrared drying of okra. Infrared radiation (IR) power (62, 74, 88 and 104 W) as drying parameter is evaluated on drying characteristics of okra. The infrared power affected the drying and colour characteristics of okra. Drying time was found decreasing with increase in infrared power. Four thin-layer drying models were evaluated for moisture ratios using nonlinear regression analysis. The results of regression analysis indicated that the Midilli & Kucuk model gave the excellent fit for the drying data under all drying conditions with the lowest chi(2) and RMSE values and highest R-2 value. The effective moisture diffusivity at each infrared power was determined by Fick's second law of diffusion, an increase in the power led to increase in the effective moisture diffusivity between 8.54x10(-10) and 2.32x10(-9) m(2)/s. The dependence of effective moisture diffusivity on infrared power was expressed by a modified Arrhenius type equation. Activation energy was estimated as 3.91 kW/kg.
Keywords: Activation energy; effective moisture diffusivity; infrared drying; mathematical modelling; okra; MOISTURE DIFFUSIVITY; ENERGY-CONSUMPTION; MASS-TRANSFER; QUALITY; Engineering